Randomized, single-blind, placebo-controlled trial on Hominis placenta extract pharmacopuncture for hot flashes in peri- and post-menopausal women - Su-Ji Choi; Dong-Il Kim; Sang Ho Yoon; Chang-Min Choi; Jeong-Eun Yoo (Integrative Medicine Research)
Background: Hominis placenta pharmacopuncture is widely used for climacteric symptoms. This study examined the efficacy and safety of pharmacopuncture with PLC (the extract of Hominis placenta) on hot flashes for perimenopausal and postmenopausal women. Methods: This study was a randomized placebo-controlled single-blind trial, which recruited 128 perimenopausal and postmenopausal women, randomly assigned to receive pharmacopuncture with PLC or normal saline (NS) for eight weeks. The primary outcome was the mean changes in the hot flash score (HFS) and the secondary outcomes were the mean changes in the Menopause Rating Scale (MRS), follicle-stimulating hormone (FSH) levels, and estradiol (E2) levels from baseline to eight weeks. Missing values were imputed using the last-observation-carried-forward method. Results: After treatment (week 9), the HFS decreased significantly in both groups (p = 0.000). The residual HFS was 47.09 ± 41.39% and 56.45 ± 44.92 % in the PLC and control groups, respectively (p = 0.262). One month after the treatment (week 13), the score of the PLC group was reduced, but the score increased in the control group (p = 0.077). There were no statistically significant differences in the mean changes in MRS, FSH, and E2 between the two groups. No serious adverse events related to this trial were noted. Conclusion: In this study, Hominis placenta extract pharmacopuncture did not differ significantly from NS in reducing the hot flash score. While this therapy appears safe, the potential for long-term effect of PLC extract needs to be examined in a large randomized controlled trial with appropriate controls. Trial registration: Clinical Research Information Service, Republic of Korea, KCT0 0 03533.